Method for preparing aerogel from coal gas fine slag high-carbon component
The high-carbon components in the gasified fine slag were separated by isodenative gradient centrifugation technology, and carbon aerogels and graphene aerogels were prepared through processes such as acid leaching, chemical activation and oxidation intercalation, which solved the problems of low resource utilization rate of coal gasified fine slag and environmental pollution, and achieved efficient resource utilization and low-cost preparation.
Patent Information
- Application Number
- CN202411903202.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to efficiently utilize the high-carbon components in the fine coal gasified slag, resulting in low resource utilization and environmental pollution problems.
The high-carbon components in the gasified fine slag were separated into light carbon and heavy carbon by isodenal gradient centrifugation technology, and carbon aerogels and graphene aerogels were prepared by acid leaching, chemical activation and oxidation intercalation processes, respectively.
It has achieved efficient resource utilization of high-carbon components of coal gasified fine slag, improved the resource utilization value of coal-based solid waste, reduced the raw material cost in the preparation process of aerogel, and helped the development of green chemical industry and circular economy.
Smart Images

Figure CN119706819A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high value-added resource utilization of coal-based solid waste and preparation of carbon-based aerogels, and specifically relates to a method for preparing aerogels by utilizing high-carbon components of coal gasification fine slag. Background Art
[0002] Coal gasification technology has been rapidly developed as a key technology to promote the clean, efficient and green use of coal. However, the annual emission of coal gasification slag produced in the coal gasification process has exceeded 70 million tons. Since coal gasification slag contains rich unburned carbon and other inorganic components, it has long been regarded as a potential resource. However, at present, the treatment of coal gasification slag in my country is mainly landfilling and stacking, which not only occupies land resources, but also may cause environmental pollution of heavy metals and ash. With the improvement of environmental protection requirements and the continuous growth of demand for high-performance new materials, how to efficiently utilize the high-carbon components in coal gasification slag has become an urgent problem to be solved.
[0003] Carbon aerogel is a porous, amorphous nanocarbon material with a high specific surface area and excellent electrical conductivity, while graphene aerogel is mainly composed of graphene and has a three-dimensional porous network structure, combining the nano properties of graphene with the macroscopic structural characteristics of aerogel. Graphene aerogel is widely used in energy storage, catalyst carriers and adsorption materials due to its excellent electrical conductivity, mass transfer rate and mechanical stability. The residual carbon in coal gasification slag is mainly amorphous carbon and graphitized carbon. These high-carbon components have high carbon content and unique physical and chemical properties, which can provide an important source of raw materials for the preparation of high value-added carbon materials. By applying the high-carbon components in coal gasification slag to carbon aerogel and graphene aerogel, it can not only realize the resource utilization of coal gasification slag and reduce environmental pollution, but also provide new ideas and approaches for the research and development of functional materials.
[0004] A Chinese patent (CN 117963900 A) discloses a method for preparing graphene using coal gasification slag, which includes pre-oxidizing coal gasification slag with a high carbon content, mixing it with a strong acid and an oxidant in proportion, and dissolving the aluminosilicate minerals in the slag during oxidation and intercalation of the graphitized carbon residue in the slag. On this basis, graphene is obtained after reduction with an alkaline solution.
[0005] Compared with the patent (CN117963900A), the present application separates the high carbon components of coal gasification fine slag ash with a content of less than 30%, synthesizes carbon aerogel from light carbon, and synthesizes graphene aerogel from heavy carbon. The patent (CN117963900A) describes a method for preparing graphene.
[0006] This application aims to solve how to separate and utilize high-carbon components with ash content less than 30% in coal gasification fine slag, and to achieve efficient preparation of carbon aerogel and graphene aerogel by separating light carbon from heavy carbon. After the preparation of graphene oxide (CGO), this patent further realizes the preparation of graphene aerogel through a process of chemical reduction combined with strong alkali intercalation. This patent focuses on the preparation process of three-dimensional graphene aerogel, and ensures the uniformity of the pore structure and specific surface area of the aerogel through steps such as intercalation and ultrasonic treatment. The patent (CN117963900A) mainly focuses on the oxidation and purification process of carbon in coal gasification slag for the preparation of graphene, and does not involve how to refine the separation of high-carbon components, and does not explicitly mention the continuous preparation process of carbon aerogel and graphene aerogel. It only describes the process of obtaining graphene through oxidation intercalation and alkaline solution reduction. The process of the patent (CN117963900A) focuses on the reduction operation of two-dimensional graphene, and does not involve the preparation process of aerogel and related performance optimization.
[0007] This application pre-treats the coal gasification fine slag by gravity separation or flotation, and then uses isopycnic gradient centrifugation technology to further separate the high carbon components with ash content less than 30% into light carbon and heavy carbon. The light carbon is prepared by acid leaching to remove impurities, chemical activation to regulate the pore structure, etc. to obtain carbon aerogel (this is the so-called technical means mentioned in patent CN117963900A). Heavy carbon is used to prepare graphene aerogel. After the preparation of graphene oxide (CGO), this patent further realizes the preparation of graphene aerogel through the process of chemical reduction combined with strong alkali intercalation: CGO is formulated into a uniform dispersion (1-10 mg / mL) and dispersed by ultrasound; strong alkali intercalation is added in a ratio of 2:1-5:1, mixed evenly and dried at room temperature to prepare a graphene aerogel precursor; the precursor is calcined at high temperature, and then acid washed, filtered and dried at normal pressure to finally prepare graphene aerogel. The process path is clear, the steps are clear, and the innovative technical means of isopycnic gradient centrifugation is emphasized. The patent (CN117963900A) only describes the technical route of obtaining graphene through carbon oxidation treatment, and does not involve the process of separating and utilizing the high-carbon components in coal gasification slag, let alone how to prepare carbon aerogel and graphene aerogel respectively. The technical solution of this application specifically improves the resource utilization efficiency of coal gasification slag, which is significantly different from the single graphene preparation method of the patent (CN117963900A).
[0008] This application further refines the separation of high-carbon components through the technical means of isopycnic gradient centrifugation, breaking through the limitations of traditional flotation or gravity separation methods. This innovative technology ensures the efficient separation of light carbon and heavy carbon, thereby providing a higher purity raw material guarantee for the subsequent preparation of carbon aerogel and graphene aerogel. In the patent (CN117963900A), flotation or gravity separation is only used as a pretreatment method, and no further optimization of the separation technology or exploration of the subsequent utilization path of the separation is made. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing aerogel using high-carbon components of coal gas slag. The method converts high-carbon components in coal gasification slag into high-value-added carbon materials through separation and impurity removal, oxidation intercalation, chemical reduction and other processes, thereby solving the problems of low resource utilization rate and environmental pollution of coal gasification slag. The present invention efficiently separates and deeply utilizes high-carbon components in coal gasification slag, realizes the high-value conversion of high-carbon resources in slag, provides a synthetically innovative technical path for the preparation of high-value-added functional materials of coal gasification slag, and provides a theoretical basis and technical support for the development of clean energy and the construction of a circular economy.
[0010] The technical solution adopted by the present invention is a method for preparing aerogel using high-carbon components of coal gas fine slag, comprising the following steps:
[0011] (1) First, the coal gasification fine slag is crushed and dissociated, and a high carbon component with an ash content of less than 30% is separated by gravity separation or flotation. Then, the high carbon component is separated into light carbon mainly composed of an amorphous carbon structure and heavy carbon mainly composed of a graphitized structure by isopycnic gradient centrifugation to provide raw materials for subsequent preparation;
[0012] (2) The light carbon obtained in step (1) is subjected to acid leaching to remove impurities, and then chemically activated with a strong base to adjust the pore structure of the light carbon, and then washed with acid and dried at normal pressure to obtain a carbon aerogel;
[0013] (3) The heavy carbon obtained in step (1) is first subjected to oxidation exfoliation and intercalation using a strong acid to obtain coal gasification slag-based graphene oxide (CGO) (graphene precursor), and then chemically reduced, acid washed, and dried at normal pressure to obtain graphene aerogel.
[0014] Preferably, in step (1), the coal gasification fine slag comes from a coal gasification plant, regardless of the gasification process and the type of gasified coal; the carbon ash components are separated by crushing, dissociation, gravity separation or flotation to obtain a high-carbon component with an ash content of less than 30%; the obtained low-carbon component can be used on a large scale as a building material or mine filling material.
[0015] Preferably, in the step (1), during the process of separating the high carbon component into light carbon and heavy carbon by isopycnic gradient centrifugation, 1 g of the high carbon component with an ash content of less than 30% and 40 mL of anhydrous ethanol are placed in a centrifuge tube, ultrasonically vibrated for 10 min-1 h, and then separated using a centrifuge, 20 mL of the suspension is poured out and filtered to obtain light carbon; then anhydrous ethanol is continued to be added to the centrifuge tube, and the ultrasonic oscillation and centrifugation steps are repeated until the suspended particles are small and a transparent supernatant is presented, and finally the separated sediment is heavy carbon.
[0016] The isopycnic gradient centrifugation method includes a floating and sinking experiment and an ultrasonic-assisted centrifugation method; the ultrasonic-assisted centrifugation method includes ultrasonic treatment and centrifugal separation performed in sequence, the separation medium is pure water and anhydrous ethanol, and the ultrasonic treatment time is 10-30 minutes; the ultrasonic-assisted centrifugation method is treated 1-5 times.
[0017] Preferably, in the step (2), in the acid leaching and impurity removal process of the light carbon, a strong acid reagent is mixed with the light carbon in proportion, placed in a magnetic stirrer, the temperature is adjusted to 50-90° C., the acid leaching time is 1-2 h, and then washed with pure water, filtered, and dried to obtain the light carbon after impurity removal; the strong acid reagent includes: any one or a combination of hydrochloric acid, nitric acid or hydrofluoric acid.
[0018] Preferably, in step (2), a strong base is used for chemical activation to regulate the pore structure: 1 g of the impurity-removed light carbon is ground and mixed with 1-5 g of a strong base until there are no white particles, and then the mixture is allowed to stand for 12 hours, and then calcined at a high temperature under a nitrogen atmosphere. The product is then acid-washed, filtered, and dried at normal pressure to obtain a carbon aerogel; the strong base includes any one of sodium hydroxide and potassium hydroxide, or a combination of both.
[0019] Preferably, in the step (2), a strong base is used for chemical activation to regulate the pore structure: 1 g of the light carbon after impurities removal is mixed evenly with 1-5 g of a strong base and 10 ml of pure water, placed in a magnetic stirrer for immersion activation for 0.5-2 h, then poured into 10 ml of anhydrous ethanol and placed in an oven for drying for 12 h, calcined at high temperature under a nitrogen atmosphere, and then the product is acid-washed, filtered, and dried at normal pressure to obtain a carbon aerogel; the strong base includes: any one or a combination of sodium hydroxide and potassium hydroxide.
[0020] Preferably, in the step (3), in the process of using a strong acid to oxidatively exfoliate and intercalate heavy carbon to obtain coal gasification slag-based graphene oxide (CGO), the strong acid and heavy carbon are mixed in proportion, and magnetic stirring is performed at room temperature for 2-8 hours to oxidatively exfoliate and intercalate graphitized carbon, and then washed with pure water and dried to obtain coal gasification slag-based graphene oxide (CGO); the strong acid includes: any one or a combination of sulfuric acid, hydrochloric acid or nitric acid.
[0021] Preferably, in the step (3), the graphene aerogel is obtained after chemical reduction, acid washing and drying at normal pressure: 1-10 mg / mL CGO dispersion is prepared by anhydrous ethanol and ultrasonic dispersion is used to uniformly disperse it, a strong base and CGO are added to the CGO dispersion in a ratio of 2:1-5:1, mixed evenly and dried at room temperature to obtain a graphene aerogel precursor, and then calcined at high temperature, and the obtained product is acid washed, filtered and dried at normal pressure to obtain the graphene aerogel; the strong base includes: any one or a combination of sodium hydroxide and potassium hydroxide.
[0022] The beneficial effects of the present invention are:
[0023] The present invention uses the high carbon components of coal gasification slag as raw materials, and successfully prepares carbon aerogel and graphene aerogel with excellent pore structure and good performance through multiple processes such as separation and impurity removal, oxidation intercalation, and chemical reduction. This patented technology gives full play to the composition and structural advantages of the high carbon components of coal gasification slag, significantly improves the resource utilization value of coal-based solid waste, and provides an innovative technical path for realizing the high-value utilization of coal gasification slag. At the same time, the present invention effectively reduces the raw material cost in the aerogel preparation process, and promotes the development of green chemical industry and circular economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a process flow chart of preparing aerogel using high carbon components of coal gasification fine slag according to the present invention;
[0025] Figure 2 This is a SEM image of carbon aerogel prepared from the lightweight carbon of the present invention;
[0026] Figure 3 N is the carbon aerogel prepared in the present invention. 2- Adsorption-desorption curve;
[0027] Figure 4 This is a SEM image of coal gasification slag-based graphene oxide prepared from heavy carbon according to the present invention;
[0028] Figure 5 This is a SEM image of the graphene aerogel prepared from the heavy carbon of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is explained in detail with reference to the specific embodiments and drawings described below.
[0030] Example 1
[0031] like Figure 1 As shown, this embodiment provides a method for preparing aerogel using high-carbon components of coal gas fine slag, comprising the following steps:
[0032] (1) First, the coal gasification fine slag is crushed and dissociated, and a high carbon component with an ash content of less than 30% is separated by gravity separation or flotation. Then, the high carbon component is separated into light carbon mainly composed of an amorphous carbon structure and heavy carbon mainly composed of a graphitized structure by isopycnic gradient centrifugation to provide raw materials for subsequent preparation;
[0033] In step (1), the coal gasification fine slag comes from the Ningdong coal chemical base, and is crushed and dissociated by wet ball milling for 8 minutes, and then a high carbon component with an ash content of 27% is obtained by flotation.
[0034] In step (1), during the process of separating the high carbon component into light carbon and heavy carbon by isopycnic gradient centrifugation technology, 1g of high carbon component with ash content of 27% and 40mL of anhydrous ethanol are placed in a centrifuge tube, ultrasonically vibrated for 20 minutes, and then separated by a centrifuge, the separation time is set to 10 minutes, the speed is 2500r / min, and 20mL of the suspension is poured out and filtered to obtain light carbon. Then continue to add 20mL of anhydrous ethanol to the centrifuge tube, repeat the above ultrasonic vibration and centrifugation steps 4 times, until the suspended particles are small, a transparent supernatant is presented, and finally the sediment obtained by separation is heavy carbon.
[0035] (2) The light carbon obtained in step (1) is subjected to acid leaching to remove impurities, and then chemically activated with a strong base to adjust the pore structure of the light carbon, and then washed with acid and dried at normal pressure to obtain a carbon aerogel;
[0036] In step (2), in the acid leaching and impurity removal process of the light carbon, hydrochloric acid and hydrofluoric acid (1:3) are mixed with the light carbon in a ratio of 4:1, and the mixture is placed in a magnetic stirrer, the temperature is adjusted to 55°C, the acid leaching time is 1.5 hours, and then the mixture is washed with pure water, filtered, and dried in a vacuum drying oven at 105°C for 6 hours to obtain the light carbon after impurity removal;
[0037] In step (2), strong alkali is used for chemical activation to regulate the pore structure: 1 g of the impurity-free light carbon is ground and mixed with 3 g of potassium hydroxide until there are no white particles, and then the mixture is allowed to stand for 12 hours, and then calcined at high temperature in a nitrogen atmosphere, with a heating rate of 5 ° C / min, and the temperature is raised to 750 ° C. After keeping the temperature for 120 minutes, the mixture is cooled to room temperature with the furnace, and then the product is acid-washed, filtered, and dried in a vacuum drying oven at 105 ° C for 6 hours to obtain a carbon aerogel (such as Figure 2 ). N of carbon aerogel 2- The adsorption-desorption curve is Figure 3 As shown, the specific surface area can reach 1345.12m 2 / g;
[0038] (3) The heavy carbon obtained in step (1) is first subjected to oxidation exfoliation and intercalation using a strong acid to obtain coal gasification slag-based graphene oxide (CGO) (graphene precursor), and then chemically reduced, acid washed, and dried at normal pressure to obtain graphene aerogel.
[0039] Example 2
[0040] This embodiment provides a method for preparing aerogel using high carbon components of coal gasification fine slag, referring to the method described in Example 1, except that:
[0041] In the step (2), strong alkali is used for chemical activation to regulate the pore structure: 1 g of the light carbon after impurities removal is mixed evenly with 3 g of strong alkali and 10 ml of pure water, placed in a magnetic stirrer for immersion activation for 1.5 h, then poured into 10 ml of anhydrous ethanol and placed in an oven for drying for 12 h, and high-temperature calcined in a nitrogen atmosphere at a heating rate of 5°C / min, heated to 750°C, kept warm for 120 min, and then cooled to room temperature with the furnace, and then the product is acid-washed, filtered, and placed in a 105°C vacuum drying oven for 6 h to obtain a carbon aerogel.
[0042] Example 3
[0043] This embodiment provides a method for preparing aerogel using high carbon components of coal gasification fine slag.
[0044] In the step (3) of the present invention, in the process of using a strong acid to oxidatively exfoliate and intercalate heavy carbon to obtain coal gasification slag-based graphene oxide (CGO), sulfuric acid and nitric acid (1:3) are mixed with heavy carbon in a ratio of 4:1, and magnetic stirring is performed at room temperature for 2 hours to oxidatively exfoliate and intercalate graphitized carbon, and then washed with pure water and placed in a vacuum drying oven at 105°C for 6 hours to obtain coal gasification slag-based graphene oxide (CGO) (such as Figure 4 ); chemical reduction, acid washing, and normal pressure drying to obtain graphene aerogel: 10 mg / mL CGO dispersion was prepared with anhydrous ethanol and uniformly dispersed using ultrasound (15 min), CGO and strong alkali were added to the CGO dispersion at a ratio of 3:1, mixed evenly, and dried at room temperature to obtain a graphene aerogel precursor, which was then calcined at high temperature, and the obtained product was acid-washed, filtered, and dried in a vacuum drying oven at 105°C for 6 h to obtain a graphene aerogel (such as Figure 5 ).
[0045] The applicant declares that the above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. The technicians in the technical field should understand that any changes or substitutions that can be easily thought of by the technicians in the technical field within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing aerogel using high carbon components of coal gas fine slag, characterized in that: The following steps are involved: (1) First, the coal gasification fine slag is crushed and dissociated, and a high carbon component with an ash content of less than 30% is separated by gravity separation or flotation. Then, the high carbon component is separated into light carbon mainly composed of an amorphous carbon structure and heavy carbon mainly composed of a graphitized structure by isopycnic gradient centrifugation to provide raw materials for subsequent preparation; (2) removing impurities from the light carbon obtained in step (1) by acid leaching, chemically activating the light carbon using a strong base to adjust the pore structure of the light carbon, and then washing with acid and drying at normal pressure to obtain a carbon aerogel; (3) The heavy carbon obtained in step (1) is first subjected to oxidation exfoliation and intercalation using a strong acid to obtain CGO, and then subjected to chemical reduction, acid washing, and normal pressure drying to obtain graphene aerogel.
2. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 1, characterized in that: In the step (1), the coal gasification fine slag comes from a coal gasification plant, regardless of the gasification process and the type of gasified coal.
3. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 2, characterized in that: In the step (1), during the process of separating the high carbon component into light carbon and heavy carbon by isopycnic gradient centrifugation, 1 g of the high carbon component with an ash content of less than 30% and 40 mL of anhydrous ethanol are placed in a centrifuge tube, ultrasonically vibrated for 10 min-1 h, and then separated using a centrifuge, 20 mL of the suspension is poured out and filtered to obtain light carbon; then anhydrous ethanol is continued to be added to the centrifuge tube, and the ultrasonic vibration and centrifugation steps are repeated until the suspended particles are small and a transparent supernatant is presented, and finally the separated sediment is heavy carbon.
4. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 3, characterized in that: The isopycnic gradient centrifugation method includes a floating and sinking experiment and an ultrasonic-assisted centrifugation method; the ultrasonic-assisted centrifugation method includes ultrasonic treatment and centrifugal separation performed in sequence, the separation medium is pure water and anhydrous ethanol, and the ultrasonic treatment time is 10-30 minutes; the ultrasonic-assisted centrifugation method is treated 1-5 times.
5. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 1, characterized in that: In the step (2), during the acid leaching and impurity removal process of the light carbon, a strong acid reagent is mixed with the light carbon in proportion, placed in a magnetic stirrer, the temperature is adjusted to 50-90° C., the acid leaching time is 1-2 hours, and then washed with pure water, filtered, and dried to obtain the light carbon after impurity removal; the strong acid reagent includes: any one or a combination of hydrochloric acid, nitric acid or hydrofluoric acid.
6. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 5, characterized in that: In the step (2), a strong base is used for chemical activation to regulate the pore structure: 1 g of the impurity-removed light carbon is ground and mixed with 1-5 g of a strong base until there are no white particles, and then the mixture is allowed to stand for 12 hours, and then calcined at high temperature under a nitrogen atmosphere. The product is then acid-washed, filtered, and dried at normal pressure to obtain a carbon aerogel; the strong base includes any one of sodium hydroxide and potassium hydroxide, or a combination of both.
7. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 5, characterized in that: In the step (2), a strong base is used for chemical activation to regulate the pore structure: 1 g of the light carbon after impurities removal is mixed evenly with 1-5 g of a strong base and 10 ml of pure water, and the mixture is placed in a magnetic stirrer for immersion activation for 0.5-2 h, and then 10 ml of anhydrous ethanol is poured into the mixture and dried in an oven for 12 h, and then the mixture is calcined at a high temperature under a nitrogen atmosphere, and then the product is acid-washed, filtered, and dried at normal pressure to obtain a carbon aerogel; the strong base includes: any one of sodium hydroxide and potassium hydroxide or a combination of two.
8. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 1, characterized in that: In the step (3), in the process of using a strong acid to oxidatively exfoliate and intercalate heavy carbon to obtain CGO, the strong acid and heavy carbon are mixed in proportion, and magnetic stirring is performed at room temperature for 2-8 hours to oxidatively exfoliate and intercalate graphitized carbon, and then washed with pure water and dried to obtain CGO; the strong acid includes: any one or a combination of sulfuric acid, hydrochloric acid or nitric acid.
9. The method for preparing aerogel using high carbon components of coal gas fine slag according to claim 8, characterized in that: In the step (3), the graphene aerogel is obtained after chemical reduction, acid washing and normal pressure drying: 1-10 mg / mL CGO dispersion is prepared by anhydrous ethanol and ultrasonic dispersion is used to uniformly disperse it, a strong base and CGO are added to the CGO dispersion in a ratio of 2:1-5:1, mixed evenly and dried at room temperature to obtain a graphene aerogel precursor, and then calcined at high temperature, and the obtained product is acid washed, filtered and dried at normal pressure to obtain the graphene aerogel; the strong base includes: any one or a combination of sodium hydroxide and potassium hydroxide.
Citation Information
Patent Citations
Preparation method of high-specific-surface-area high-electric-conductivity graphene compound carbon aerogel based on chemical crosslinking
CN106365142A
Auxiliary cementing material based on coal gasification fine ash and preparation method thereof
CN116854388A
Modified high-carbon coal gasification slag as well as preparation method and application thereof
CN116967251A
Method for preparing graphene from coal gasification slag
CN117963900A
Method for preparing graphene using coal as raw material
US20180155201A1
Cited By
Coal gasification slag-based aerogel porous material and application thereof
CN121362366A
Mechanically activated coal gasification slag-based cementing material and preparation method thereof
CN121517133A
Coal gasification slag-based aerogel porous material as well as preparation method and application thereof
CN122352227A
Coal gasification fine slag-based imitation brain fold aerogel porous material and application
CN122582852A